Economic evaluation of the screening for Alzheimer’s disease in China - Ren, Yinan; Zhou, Dachuang; Xing, Qian; Gong, Fangfang; Tang, Wenxi (Frontiers in Aging Neuroscience, 2022)
Background We evaluated the cost-effectiveness of the screening in mainland China for Alzheimer’s disease (AD) patients aged over 60. Methods Individuals in mainland China, received an initial screening by questionnaire on mental state, and those with scores deemed suspicious for AD were referred to diagnostic tests. A 9-state Markov model was developed to simulate the disease progression of a cohort of 100,000 subjects aging from 60 to 80. In addition, several scenarios were analyzed to assess the robustness under different screening frequency, starting age, the duration of drug effects, and the health status of subjects. Results The ICER of AD screening was 26413.77 USD per QALY [quality-adjusted life-year (QALY)] compared with no screening. The number of deaths and severe AD cases who did not receive treatment averted by screening accounted for 0.076 and 0.006% of the total population, respectively, and the net monetary benefit was 128.29 USD per capita. Under the thresholds of one and three times the gross domestic product per capita, the probability of screening being cost-effective was approximately 18 and 77%, respectively. The ICER decreased to 18132.96USD per QALY when the drug effect was prolonged, and increased when the frequency of screening was increased, the starting age was postponed, and patients suffering from comorbidities were more. However, the number of severe AD cases and deaths declined when the screening frequency increased. Conclusion Screening for AD in individuals over 60 can reduce the numbers of severe AD cases and deaths and may be cost-effective, depending on factors such as screening frequency, starting age of screening, and duration of drug effects. Additionally, mild cognitive impairment (MCI) is an important stage at which the burden of progression to AD may be reduced and the cost-effectiveness of screening may be improved.